The opiate receptor: a model explaining structure-activity relationships of opiate agonists and antagonists. - Feinberg, A P (1976)
A model of the opiate receptor is proposed which explains structure-activity relationships of opiate drugs, including (i) the unique potency of certain opiates such as etonitazene, fentanyl, phenazocine, and oripavines; (ii) the role of N-allyl substituents in conferring antagonist properties; and (iii) chemical features that afford "pure" antagonists. The model indicates mlecular mechanisms for interconversion of the opiate receptor between respective states that bind agonists or antagonists with high affinity.